2020
DOI: 10.1108/ijis-08-2019-0083
|View full text |Cite
|
Sign up to set email alerts
|

Reaching sustainability during a digital transformation: a PLS approach

Abstract: Purpose In a world where big data have become crucial to guarantee the success of companies, digital transformation came to help companies transition towards a digital business and accept the changes in the organizational structure as well as the market. Nonetheless, even with the ever-growing importance shed on it, few articles and studies have linked it to the sustainability paradigm. Empirical studies that have linked between the factors of digital transformation and a more sustainable business are still sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 51 publications
2
44
0
2
Order By: Relevance
“…Second, it assesses the relationship between digital transformation and the SDGs. Finally, the research sample is made up of Italian firms, which have not previously been examined [7,20]. This study's findings underline a positive relationship between a firm's digital transformation and its orientation toward the Sustainable Development Goals; the empirical results show an increasing transition in Italian firms toward meeting the SDGs during 2016-2019.…”
Section: Introductionmentioning
confidence: 74%
“…Second, it assesses the relationship between digital transformation and the SDGs. Finally, the research sample is made up of Italian firms, which have not previously been examined [7,20]. This study's findings underline a positive relationship between a firm's digital transformation and its orientation toward the Sustainable Development Goals; the empirical results show an increasing transition in Italian firms toward meeting the SDGs during 2016-2019.…”
Section: Introductionmentioning
confidence: 74%
“…In particular, the combination of corporate sustainability and digitalisation helps transform the organisational nature of banks by simultaneously narrowing their boundaries and expanding their scope. El Hilali et al [42] drew attention to possible ways of reaching sustainability during digital transformation processes. They found that the companies achieved sustainability when effectively mastering customers, data processing, and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al. [9]-which showed that customers, data and innovation, are drivers, and that companies should use marketing tools during a digital transformation-has a significant impact on companies' quest to reach sustainability. The digital transformation is to embrace sustainability, because it requires radical changes in strategy and the business model level.…”
Section: Introductionmentioning
confidence: 99%